Memória e identidade em Jaguariaíva, Paraná: contribuição à cartografia escolar - Calandro, Thiago Luiz [UNESP] (2015)
In a globalized world, more and more necessary is done to study the regional and local identities in order to promote their valuation and form active citizens in all spatial scales. This work carries out a discussion which approaches the memory with spatial representations made by elementary school students in the city of Jaguariaiva, Paraná, Brazil. Cultural identities are treated as meaning production instance regarding living spaces. The relations between formal education, especially the curriculum selected by school geography, and the knowledge of lived experience, can contribute to the study of references and spatial horizons of residents of urban and rural regions. This perspective is proposed as discussion which aims to contribute to the advancement of thinking about the relationship between school mapping and the production of sense of belonging to different locations. In this sense, looking repoder two questions: how the experiences, interpreted and reconstructed in the city of Jaguariaiva, Paraná, interfere with the image construction of student living space? And how these spatial representations of the students, who are loaded impressions and experiences can contribute to the study of Cartography School? we did an analysis of the productions that students have developed from some activities, with the spatial reference the city of Jaguariaiva, Paraná Brazil, from the perspective of memory. Assuming that the representation of space is interactive, multiple and open the space image studies and the memory from activities with children, they pointed to a place that updates, rebuilds, constantly reshapes and supports numerous representations from social interactions. In this way, space is the result also of imagination, necessary for the continuity of multiple, non-synchronous and political practices in space. Under the School Cartography, the relationship memory, space and predictions present can contribute to student...